Analisis Manajemen Strategi Eksternal dan Internal dalam Pengembangan UMKM : Studi Kasus pada Es Teh Poci - Tiara Apriani; Muhammad Gibran Siregar; Farhan Mukti Mutakin; Rafli Maulana Yusuf; Aufa Zulfikar Maulana; Siti Mardiana (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the internal and external conditions of the Es Teh Poci business in Panyileukan, Bandung, as a strategic case study of a micro, small, and medium enterprise (MSME) in the soft drink sector. Using a descriptive qualitative approach, data were collected through semi-structured interviews with the business owner and supported by recent scholarly literature. The analysis employed several strategic frameworks, including PESTLE, Porter’s Five Forces, Competitor Mapping, Industry Matrix, EFAS, IFAS, IE Matrix, as well as internal analysis tools such as VRIO, Value Chain, Business Model Canvas, and TOWS Matrix. The findings reveal that Es Teh Poci has advantages in its distinctive taste, affordable pricing, and customer loyalty. However, it also faces challenges such as intense market competition and limited digital promotion. A differentiation strategy focused on product quality and service is essential to maintain its position in the local market. Based on the IE Matrix, the business is positioned in the “Grow and Build” quadrant, suggesting that efforts should be directed toward strengthening internal capabilities—particularly in digital marketing and product innovation—to seize external opportunities amid the rising trend of modern beverage consumption